Training on Making Power Point-Based Learning Videos for Teachers at SMKN 26 Central Jakarta - Agoestyowati, Redjeki; Hani, Umi (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The development of technology and information today requires teachers to be able to take advantage of computer technology. Students are expected to be able to obtain information from various sources, including from teachers, so teachers are required to always be able to give their best so that students are able to absorb knowledge well. The knowledge that students gain in learning includes knowledge. The use of learning media using power points has still not been maximized by all teachers at SMKN 26 Jakarta. Therefore, it is necessary to have training in making learning videos from Power Point with the aim of developing teachers' insight in making video learning media through attractive power point animations in an easy way. This training was attended by 80 teachers of SMKN 26 Jakarta with the title How to Make a Simple Learning Video from Power Point. As a result of this training, there was an increase in the competence and ability of teachers in making teaching materials. Their Video Work can be used for teaching and is one of the most contemporary learning media.